Análisis jurídico de las falencias en el procedimiento administrativo de la adopción. - Ayala Garcés, Lilibeth Corazón (2015)
This work will aim to conduct a theoretical-doctrinaire, from a case, legal analysis of the shortcomings of the administrative procedure of adoption, circumstances that violate constitutional rights and guarantees enshrined through the constitutional principle called the principle of interests of the child and adolescent. It is noteworthy that while it is true, our legislation provides and establishes the legal concept of adoption; in practice, the application of the procedure for verification, specifically within the administrative, presents a number of difficulties and obstacles to a speedy, efficient and timely process. In this context, the development of this research reveals a series of delays, obstacles and neglect at the appropriate level, represent an impediment to the effective operation; with which it aims to highlight the need to correct, improve and, if appropriate, procedurally regulate this legal institution, in order to prevail in its process the principles of efficiency, effectiveness and timeliness. From the above, once identified the existing problems, it is proposed as a contribution of research to make a proposal for a legislative scope, so that the procedure in question is verified in a framework of effectiveness, efficiency and timeliness procedure that guarantees the prevalence of the principle Best Interest of the Child and the right to a decent life assured to all children and adolescents.